KOLABORASI MULTIDISIPLIN DAN HIBRIDITAS KREATIF DALAM DESAIN VTUBER SEBAGAI MEDIA KOMUNIKASI VISUAL IMERSIF PENGENALAN KAMPUS - Ajeng Tita Negoro; Nurhadi Nurhadi (Institut Seni Indonesia Yogyakarta, 2026)
The VTuber (Virtual YouTuber) phenomenon has emerged as an innovative interactive visual communication design agent in the multiplatform digital era. This research aims to examine VTubers as a manifestation of creative hybridity that integrates character design, interactive digital animation technology, and visual communication strategies, focusing on the design of the VTuber character